A new 24 h ELISA culture based method for Helicobacter pylori chemosusceptibility. Issue 7 (31st May 2010) - Perna, Federico; Vaira, Dino
Abstract : Background: Clarithromycin (CH) and metronidazole (MZ) are routinely used in Helicobacter pylori treatment regimes. Recently, treatment with these antibiotics has been reported to fail in >30% of patients due to increasing resistance. The common chemosusceptibility methods are cumbersome and take up to 14 days. Chemosusceptibility of H pylori is therefore rarely checked. Aim: To develop a rapid susceptibility test (RST) for H pylori . Methods: Preliminary experiments were performed to find a broth medium able to support the growth of H pylori in 20 h and a reliable detection method to quickly detect the amount of H pylori grown in the media. A mixture of different components was the best broth medium; ELISA was chosen as the detection technique. Performance of the new RST was compared to a gold standard (break point agar dilution method). 200 consecutive patients were tested for H pylori infection and chemosusceptibility to CH and MZ by the gold standard and RST. Results: 111 patients were infected with H pylori . 105 of these were positive by both RST and the gold standard culture method; 75/105 and 68/105 strains were susceptible to CH and MZ, respectively. RST misdiagnosed 2 strains of CH and 10 strains of MZ. Conclusions: A new simple and rapid chemosusceptibility test for H pylori has been validated, which is simple to perform and reduces the procedure time from 6–14 days to 24 h.